Thyroid disorders in patients with polycystic ovarian syndrome in Benghazi - Alfalah, Omar; Ehmouda, Fathia (Benghazi University Medical Journal, 2025)
Abstract Background: Recent studies have highlighted a higher occurrence of thyroid abnormalities in women diagnosed with polycystic ovary syndrome (PCOS), although the underlying mechanisms linking the two conditions remain uncertain. Aim and Objectives: To determine the prevalence of thyroid dysfunction among patients with PCOS. Methods: A retrospective review of medical records was conducted for 116 patients attending the endocrine clinic in Benghazi medical center during the period from the first of September to the end of October 2020. Results: The mean age was (35.5±9.8 years), the mean body mass index for the study group was 31.8±6.5kg/m2. Among studied group; 81% of participants had oligomenorrhea, 97.4% had hirsutism, and 84% had ultrasound features of polycystic ovaries; Overall, the prevalence of thyroid disorders among patients with PCOS was 31%, the main thyroid disorder was autoimmune thyroiditis which represented 13.8% followed by subclinical hypothyroidism which found in 9.5% of all participants. Conclusion: More than one third of the studied group had thyroid disorders. Autoimmune thyroiditis represented the main disorder.